2011
DOI: 10.4236/jbbs.2011.13016
|View full text |Cite
|
Sign up to set email alerts
|

Brain Processing of Fearful Facial Expression in Mentally Disordered Offenders

Abstract: Emotional facial expressions are important cues for interaction between people. The aim of the present study was to investigate brain function when processing fearful facial expressions in offenders with two psychiatric disorders which include impaired emotional facial perception; autism spectrum disorder (ASD) and psychopathy (PSY). Fourteen offenders undergoing forensic psychiatric assessment (7 with ASD, and 7 psychopathic offenders) and 12 healthy controls (HC) viewed fearful and neutral faces while underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Facial expressions play a particularly important role in emotion processing (Saarni, Campos, Camras, & Witherington, 2008). In reality, an impairment in the identification of emotional facial expressions can lead to social failure and criminal behaviour (Dodge, Laird, Lochman, & Zelli, 2002;Howner et al, 2011). In fact, deficits in recognising facial expressions of emotions have been found in studies performed with antisocial populations, in general, including people with aggressive behaviour, unspecified criminals, delinquents, externalising individuals (Marsh & Blair, 2008), prisoners (Robinson et al, 2012), and in the personality disorders closely associated to criminality, such as, antisocial personality disorder (Dawel, O'Kearney, McKone, & Palermo, 2012;Dolan & Fullam, 2006;Marsh & Blair, 2008), psychopathy (Dolan & Fullam, 2006;Hastings, Tangney, & Stuewig, 2008;Marsh & Blair, 2008;Wilson, Juodis, & Porter, 2011) or borderline personality disorder (Robin et al, 2012).…”
mentioning
confidence: 98%
“…Facial expressions play a particularly important role in emotion processing (Saarni, Campos, Camras, & Witherington, 2008). In reality, an impairment in the identification of emotional facial expressions can lead to social failure and criminal behaviour (Dodge, Laird, Lochman, & Zelli, 2002;Howner et al, 2011). In fact, deficits in recognising facial expressions of emotions have been found in studies performed with antisocial populations, in general, including people with aggressive behaviour, unspecified criminals, delinquents, externalising individuals (Marsh & Blair, 2008), prisoners (Robinson et al, 2012), and in the personality disorders closely associated to criminality, such as, antisocial personality disorder (Dawel, O'Kearney, McKone, & Palermo, 2012;Dolan & Fullam, 2006;Marsh & Blair, 2008), psychopathy (Dolan & Fullam, 2006;Hastings, Tangney, & Stuewig, 2008;Marsh & Blair, 2008;Wilson, Juodis, & Porter, 2011) or borderline personality disorder (Robin et al, 2012).…”
mentioning
confidence: 98%
“…Nevertheless, contradictory data have been found in specific offender samples, for example, suggesting a physiological hyper-reactivity in those who physically abuse children (McCanne & Hagstrom, 1996) and in people with antisocial personality disorder (Iria, Barbosa, & Paixão, 2010). More recently, a neuroimaging study also found contradictory data suggesting that offenders have enhanced neural processing of fearful faces in the amygdala as well as in other facial processing brain areas, compared to controls (Howner et al, 2011). Also, Seidel et al (2013) found that offenders show reduced physiological responses specifically during the identification of fear and disgust.…”
mentioning
confidence: 99%
“…Since deficits in the identification of emotions could be related to failures in social competence and the genesis of criminal behavior (Blair, Peschardt, Budhani, Mitchell, & Pine, 2006; Dodge, Laird, Lochman, & Zelli, 2002; van Goozen, Fairchild, Snoek, & Harold, 2007; Howner et al, 2011), psychobiologic models have proposed differences in the ability to identify facial expressions in offenders and non-offenders (Dolan & Fullam, 2006; Marsh & Blair, 2008). In fact, the ability to identify facially expressed emotions seems to be associated to individual or group specificities (Iria & Barbosa, 2009; Pham & Philippot, 2010) and populations with an antisocial lifestyle (people with psychopathy and borderline personality disorder, criminal recidivists, and those suffering from behavioral disorders) frequently exhibit deficits in identifying emotions from facial expressions in general (Hastings, Tangney, & Stuewig, 2008), or negative expressions, such as fear (Blair et al, 2004) and anger (Marsh & Blair, 2008).…”
mentioning
confidence: 99%